Municipal Programs and Sustainable Development in Russian Northern Cities: Case Studies of Murmansk and Magadan - Tatiana S. Degai (MDPI AG, 2021)
Cities play an important role in promoting sustainable development. In the Arctic, most particularly in Russia, cities concentrate the majority of residents and economic activity. Sustainable development initiatives are often deployed through programs that operate at different spatial and jurisdictional scales. While national and regional policies and programs have received some attention, the understanding of urban development policies and programs at the municipal level in the Arctic is still limited. This paper presents a case study of municipal sustainable development programming in Arctic cities and examines municipal programs in two larger Russian northern cities: Murmansk and Magadan. While both are regional capitals and the most populous urban settlements in their regions, the cities have district historical, economic and geographical contexts. Through the content analysis of municipal programs active in 2018, we aim to understand, systematize and compare the visions and programmatic actions of the two municipalities on sustainable development. Ten sustainable development programming categories were identified for using a UN SDG-inspired approach modeled after the City of Whitehorse, Canada. While the programs in Magadan and Murmansk are quite different, we observed striking commonalities that characterize the national, regional and local models of urban sustainable development policy making in the Russian Arctic.